The Thesean Ritual Landscape. Appropriation, Identity and Athenian Collective Memories - Cassell, Ben S. (ARYS. Antigüedad: Religiones y Sociedades, 2020)
A key aspect of Theseus’s exponential growth in popularity between the 6th-4th cent. BCE, was an increased association with various festivals and their ritualized acts. Most prominently, it was the episode of the Cretan adventure that informed these rites. In their claimed, and emphasized, Thesean aetiologies, these festivals are revealed as vital mechanisms by which the cultural collective memory of the hero was generated. Moving beyond simply approaching ritual as an expressive mnemonic object, this paper considers the contingent and re-constructive methods by which this collective memory was produced. Moreover, by examining the embodied experience of recalling Theseus, we are provided much firmer ground in commenting on their formative force on various Athenian identities.
Keywords: collective memory; embodied cognition; identity; mnemotopography; theseus